Well-being Index Scores and Subjective Health Status of Korean Healthcare Workers - Yoonhee Shin; Bohyun Park; Nam-eun Kim; Eun Jeong Choi; Minsu Ock; Sun Ha Jee; Sue K. Park; Hyeong Sik Ahn; Hyesook Park (Korean Society for Preventive Medicine, 2022)
Objectives The aim of this study was to evaluate the subjective level of health-related quality of life of Korean healthcare workers using various quality-of-life instruments. Methods This study included 992 participants, who were doctors and nurses. A survey was conducted between November 28 and December 4, 2019. Data from 954 participants divided into 3 groups (physicians, residents, and nurses) were analyzed. Four measurement tools (29 questions) were used in the survey to evaluate subjective health status and well-being. Results In the Mayo Well-being Index, burnout during work (88.5%) and emotional difficulties caused by work (84.0%) were frequently cited by the respondents. Regarding questions on burnout and emotional difficulties, residents and nurses had the highest scores (91.0 and 89.6%, respectively). Emotional problems, such as anxiety, depression, and irritability, accounted for a high percentage (73.1%) of the total, while 82.2% of respondents reported that their work schedules interfered with their leisure and family time. There was no significant difference among the groups in subjective health status. However, 10.1% of the residents experienced very low quality of life, which was a higher proportion than that of physicians (2.7%) and nurses (5.2%). Conclusions The level of well-being that Korean medical workers experienced in relation to work was lower than the results of the United States healthcare workers surveyed using the same tool. This study was unique in that it conducted a subjective quality-of-life survey on Korean healthcare workers.